“Identificación de los riesgos laborales ocasionados por el confinamiento por Covid-19 en los estudiantes de la Universidad Técnica de Cotopaxi.” - Tello Chiliquinga, José Enrique (2021)
This research project is aimed at identifying occupational hazards, caused by confinement in students of the Technical University of Cotopaxi, with the aim of collecting information on the conditions encountered when carrying out their academic activities, through surveys applied virtually that establishes the working conditions, for later they will determine the most outstanding risks that are exposed to the students through the matrix of the Institute of Work Safety "IST"; achieving to establish a high percentage of ergonomic and psychosocial factors, due to the inadequate space and organization, which may lead to illnesses in the future, in order to offer control solutions that help reduce and prevent risks, it will be elaborated a guide to preventive measures for occupational risks in order to cultivate a culture of prevention in students.